Climatic variability in Mfabeni peatlands (South Africa) since the late Pleistocene. (15th March 2017) - Baker, Andrea; Pedentchouk, Nikolai; Routh, Joyanto; Roychoudhury, Alakendra N.
Abstract: It has been postulated that a bipolar seesaw interhemispheric mechanism dominated the relationship between the Northern and Southern hemisphere climates since the late Pleistocene. A key test for this proposition would be to undertake palaeoenvironmental studies on terrestrial archives in climatically sensitive regions. Southern Africa's contemporary C3 and C4 terrestrial plant distributions display a definitive geographical pattern dictated by different growing season rainfall and temperature zones; however, the region is generally archive poor due to its overall semi-arid climate and high relief topography. The Mfabeni peatland, with a basal age of c. 47 k yrs calibrated before present (kcal yr BP), is one of the oldest continuous coastal peat deposits in Southern Africa. Molecular leaf wax isotopes (δ 13 Cwax ) were generated for a 810 cm long core, and combined with previously published bulk geochemical (δ 13 Cbulk, %TOC), palynological, and stratigraphic data, to reconstruct the late Pleistocene and Holocene palaeoenvironments. We interpreted environmental shifts associated with the Heinrich 4, Last Glacial Maximum, deglacial and Holocene periods, which are consistent with adjacent Indian Ocean sea surface temperature records. However, the other shorter climate perturbations during the Heinrich 5, 3, 2, 1, Antarctic cold reversal and Younger Dryas, were muted, most likely due to local hydrological overprinting on the Mfabeni record. A general anti-phase sequence was observed between the Mfabeni record and better established Northern Hemisphere events, underpinning the bipolar seesaw interhemispheric mechanism proposed for global climate forcing since the Late Pleistocene. Highlights: Mfabeni peatland rare c. 47 kcal yr BP old continuous palaeoenvironment archive. Bulk C isotopes represents proportional inputs of C3 and C4 terrestrial plants. Several climate events since Late Pleistocene chronicled in the peatland archive. Shorter climate events signal absent due to local hydrological overprinting. General anti-phase trend with Northern Hemisphere climate events.